Validação de material didático para pessoas com deficiência visual: construção mútua entre usuários e projetistas - Souza, Thaís Andressa de (Universidade Federal de São Carlos, 2019)
The curricular adaptations contribute to the development of Assistive Technologies and these to support the process of Inclusive Education. The education system, at its different levels, needs to be able to provide tools that guarantee students with some form of disability access to the curriculum. This dissertation is a branch of the research project "Vertátil: Development of didactic resources for teaching and learning of people with visual impairment", which had the purpose of developing didactic resources for teaching and learning of people with visual impairment, aiming to favor the learning of these people. students. The main objective of the dissertation was to validate prototypes of didactic material for people with visual impairment, which aims at better student development. The methodology used was participant research, with survey of the necessary characteristics, exploratory visits, elaboration of 3D material, pedagogical, technical and final validation. In this sense, it was possible to emphasize the inclusive nature of the resources, which were praised by both the visually impaired and the visionaries. The results indicated that the impact of these new representations (tactical and universal perceptual didactic materials) and interactions between the involved actors (mutual project process) anticipated misuse of use, since the evaluated prototypes obtained few indications of improvement. In addition, according to the reports, the materials aroused interest and curiosity on the part of the users, aspects favorable to the learning stimulus. The validated resources were considered by the mediators of learning, offering through tactile perception the achievement of the proposed didactic objectives. Finally, the research brings a contribution of social value when presenting the possibility of equating the learnings of the students through the universal design.
Validation of didactic material for persons with visual deficiency: mutual construction between users and projetists
Keywords: Pessoas com deficiência visual; Desenho Universal; Ensino e aprendizagem; Visually impaired; Universal design; Teaching and learning; ENGENHARIAS::ENGENHARIA DE PRODUCAO